(untitled) (Journal of Educational Sciences, 2016)
In this paper, the authors have given the scientific characteristics of the problem, «the state and school education policy», which studies in the areas of pedagogy, political science, sociology, economics and jurisprudence. Based on the works of Kazakh and foreign scientists, authors systematized the theories of the concept of education policy, public policy education, school education policy and identified similarities and differences between these concepts. The authors have created a system of factors affecting the tate and school education policy. In the process of describing the elements of the system, is given a brief description of the theory of socio-economic status of state regulations in the field of education (the Constitution, the Law «On Education»), strategies and programs to promote education (Strategy «Kazakhstan – 2050», the state of program Development Reports education of Kazakhstan for 2011-2020). Based on the works of Les Belle and Howard Stevenson, the authors gave a comparative description to the periods of the implementation of educational policies.